Βιβλιοκρισία: A. CAMERON, Arguing it out.Discussion in twelfth-century Byzantium , Budapest - New York 2016 - ΧΡΥΣΟΓΕΛΟΣ Κωνσταντίνος (Byzantina Symmeikta, 2019)
Βιβλιοκρισία: A. CAMERON, Arguing it out.Discussion in twelfth-century Byzantium , Budapest - New York 2016